2021
DOI: 10.1186/s12888-021-03486-7
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation of the mental health first aid guidelines for assisting a person at risk of suicide for Sri Lanka: a Delphi expert consensus study

Abstract: Background Approximately 3000 people die by suicide each year in Sri Lanka. As family and friends may play a role in supporting a person at risk of suicide to get appropriate help, there is a need for evidence-based resources to assist with this. The aim of this study was to culturally adapt the existing English-language mental health first aid guidelines for helping a person at risk of suicide to the Sri Lankan context. Methods A Delphi expert con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The English-language items using the term ‘suicide’ or discussing with the suicidal person actions for them to get help, such as “ The first aider should demonstrate appropriate language when referring to suicide by using the terms ‘suicide’ or ‘died by suicide ’” and “ If the suicidal person is known to have a diagnosis of a mental illness, the first aider should discuss with the suicidal person what actions they should take to get help ”, were not endorsed in the Brazilian guidelines (ratings were 65 and 62%, respectively). Similar to the recently adapted suicide first aid guidelines for Sri Lanka [ 28 ], it is possible that these items received low ratings because of stigmatising attitudes towards suicide and reluctance to openly discuss it [ 34 , 35 ], as evidence shows that stigma towards mental health problems is present among health professionals in Brazil [ 13 , 14 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The English-language items using the term ‘suicide’ or discussing with the suicidal person actions for them to get help, such as “ The first aider should demonstrate appropriate language when referring to suicide by using the terms ‘suicide’ or ‘died by suicide ’” and “ If the suicidal person is known to have a diagnosis of a mental illness, the first aider should discuss with the suicidal person what actions they should take to get help ”, were not endorsed in the Brazilian guidelines (ratings were 65 and 62%, respectively). Similar to the recently adapted suicide first aid guidelines for Sri Lanka [ 28 ], it is possible that these items received low ratings because of stigmatising attitudes towards suicide and reluctance to openly discuss it [ 34 , 35 ], as evidence shows that stigma towards mental health problems is present among health professionals in Brazil [ 13 , 14 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the participants in these Delphi studies have been from high-income settings, and the cultural appropriateness for LMICs is unclear. In an effort to ensure that the guidelines are appropriate, they have been culturally adapted for China [ 27 ], Sri Lanka [ 28 ], India [ 29 ], Philippines [ 30 ], and collaborations in Brazil, Chile, and Argentina have been formed [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent adaptation of the mental health first aid guidelines for depression to the Chinese context suggests that, even though the overall guidelines remained similar to those for English-speaking countries, new actions relating to ways of respecting the autonomy of a person living with depression and the role of families were included [ 30 ]. MHFA guidelines for helping a person at risk of suicide have been adapted to the Sri Lankan context in English language only [ 31 ] and in Sinhala [ 32 ] and suggests that even though adapted guidelines are similar to the English guidelines, cultural adaptations were needed around family involvement and explicit mention of suicide. This suggests the need for specific tailoring of the MHFA guidelines on depression to the Sri Lankan context as well.…”
Section: Introductionmentioning
confidence: 99%
“…China [ 81 ], Sri Lanka [ 82 ] and Brazil [ 83 ] have recently gone through a similar process of adaptation of the English-speaking guidelines during a similar time frame, allowing for cultural comparisons, although the original English items presented to the experts in Round 1 were not identical. This study showed that in the endorsement rate in Latin American countries was lower than those in China and Sri Lanka, suggesting that cultural adaptation may have been more imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on previous studies of cultural adaptation of mental health first aid guidelines for suicide risk for China [ 81 ], Sri Lanka [ 82 ] and Brazil [ 83 ], a consortium of Chilean, Argentinian and Australian global mental health researchers and clinicians used the Delphi expert consensus methodology to culturally adapt guidelines to train lay members of the community and non-specialized health care providers interested in providing mental health first aid to someone at risk of suicide in Chile and Argentina.…”
Section: Introductionmentioning
confidence: 99%